Samuel Brohl and Company - Cherbuliez, Victor, 1829-1899 (Salt Lake City, UT : Project Gutenberg, 2006)
"Samuel Brohl and Company" by Victor Cherbuliez is a novel likely written during the late 19th century. The narrative introduces Count Abel Larinski, a disillusioned inventor, and Mlle. Antoinette Moriaz, a wealthy, independent heiress as they navigate their contrasting lives, culminating in an unexpected encounter that hints at their intertwining fates. The book seems to explore themes of ambition, despair, and the societal expectations of marriage, encapsulated in the lives of its main characters. The opening of the novel sets a tone of serendipity and fate through the simultaneous storytelling of the Count and Mlle. Moriaz. The Count, burdened by his failed weapon invention and dwindling fortunes, is at a crossroads in his life, struggling with inner demons and the looming threat of poverty. In contrast, Mlle. Moriaz enjoys a comfortable lifestyle, marked by her charitable endeavors and independence. Their initial meeting takes place in Chur, Switzerland, where destiny links them together. The narrative builds intrigue as Mlle. Moriaz grapples with her feelings towards suitors, particularly her childhood friend Camille Langis, while Abel contemplates the possibility of new beginnings shaped by love, following a painful past laced with grief and ambition. (This is an automatically generated summary.)
Release date is 2006-03-28
Produced by Dagny; John Bickers; David Widger
Keywords: France -- Fiction; Switzerland -- Fiction